Co‐integration and causality relationship between energy consumption and economic growth: Further empirical evidence for Nigeria - Ighodaro, Clement A. U. (Journal of Business Economics and Management, 2010)
The Paper re ‐ examined co‐integration and causality relationship between energy consumption and economic growth for Nigeria using data covering the period 1970 to 2005. Unlike previous related study for Nigeria, different proxies of energy consumption (electricity demand, domestic crude oil consumption and gas utilization) were used for the estimation. It also included government activities proxied by health expenditure and monetary policy proxied by broad money supply though; emphasis was on energy consumption. Using the Johansen co‐integration technique, it was found that there existed a long run relationship among the series. It was also found that all the variables used for the study were I(1). Furthermore, unidirectional causality was established between electricity consumption and economic growth, domestic crude oil production and economic growth as well as between gas utilization and economic growth in Nigeria. While causality runs from electricity consumption to economic growth as well as from gas utilization to economic growth, it was found that causality runs from economic growth to domestic crude oil production. Therefore, conservation policy regarding electricity consumption and gas utilization would harm economic growth in Nigeria while energy conservation policy as regards domestic crude oil consumption would not. Energijos suvartojimo ir ekonominio augimo tarpusavio ryšys: Nigerijos atvejo empirinis tyrimas Santrauka. Tyrinėjamas energijos suvartojimo ir ekonominio augimo tarpusavio ryšys bei priežastingumas Ni‐gerijoje, remiantis 1970–2005 m. statistiniais duomenimis. Naujai, lyginant su ankstesniais Nigerijos tyrimais, parenkami energijos vartojimo matavimo būdai (elektros energijos paklausa, vietinės naftos žaliavos suvartojimas, dujų utilizavimas). Straipsnyje atsižvelgiama į socialinę ir monetarinę valstybės politiką, kurios atspindi valstybės gerovę. Pritaikius Johansen tarpusavio priklausomybės metodą buvo gauta, kad tarp visų energijos vartojimą atspindinčių rodiklių ir ekonominio augimo yra netiesioginis priežastinis ryšys. Manoma, kad elektros bei dujų naudojimo apribojimas stabdytų Nigerijos ekonominį augimą, o naftos žaliavos vartojimo masto mažinimas nepaveiktų tolesnės šalies plėtros. Reikšminiai žodžiai: ekonominis augimas, dujų utilizavimas, naftos vartojimas, Johansen tarpusavio priklausomybės metodas. First Published Online: 14 Oct 2010